Complex system testing based on API - Milan Sliacky; Lukáš Kacar (Acta Polytechnica CTU Proceedings)
The article describes the practical experience of testing a specific ticketing system for public transport based on blockchain technology. The testing aimed to verify the overall functionality of the complex system as well as the correct execution of the functions of its selected parts, which consist of several separately developed but closely cooperating subsystems: blockchain, clearing, and mobile application subsystem with support of bank payment system. Communication between the different parts was implemented through APIs developed for this purpose. The availability of API documentation and the implementation on Linux OS allowed the use of sophisticated tools for testing and performing both manual and automated tests. Performed tests made it possible to detect errors in the program code of the respective components and to provide the basis for their elimination. Applied approaches and tools can be used to test similar complex information-handling systems.